(untitled) (NPRC Journal of Multidisciplinary Research, 2025)
The present study aimed to examine the relationship between level of education and women empowerment conducted in Mahawai Rural Municipalty of Kalikot District and Birendra Nagar Municipality of Surkhet Districts belonging to the quantitative research design. Totally 700 educated married women between 20-45 years of age group from rural (N=350) and urban areas (N=350) were randomly selected. Structured questionnaire was used as a data collection tools. The study findings revealed that the urban women demonstrated higher representation across all levels of formal education compared to rural women. The mean educational level scores were 3.29 (SD=0.95) for rural, and 3.76 (SD=0.77) for urban women, respectively, with T-value of -2.65 (p <0.05) confirmed a statistically significant difference in educational attainment favoring urban women. Mean participation scores were 3.11 (SD=0.98) and 3.31 (SD = 0.83) for rural and urban areas respectively, with a T-value of -2.31 (p < 0.05) concluded the urban women’s have significantly greater role in decision-making. Moreover, decisions dominated by husbands were more frequent in rural (34.2%) than urban (25.2%) areas. Mean scores for decision-making autonomy were 3.11 (SD=0.98) rural and 3.31 (SD=0.83) urban, with a statistically significant T-value of -2.31 (p<0.05). Education and urban exposure thus contribute positively to women’s mobility autonomy. From the results and discussion, it has been observed that the women’s education determines the acquisition of women’s empowerment.